IDENTIFIKASI IMMUNOGLOBULIN MIU (IgM) IMMUNOGLOBULIN GAMMA (IgG) ANTI SALMONELA PADA SERUM PASIEN DEMAM TIFOID DI PUSKESMAS GODEAN II, SLEMAN, YOGYAKARTA - Yuliana Prasetyaningsih; Fitri Nadifah; Desto Arisandi; Dieta Dieon Saputri (GEMA KESEHATAN, 2020)
Widal examination is a serological method to diagnose typhoid fever used by Godean II Public Health Center, Sleman Regency, Yogyakarta Special Region (DIY). However, this method is difficult to hold onto because there is no agreement on agglutination standards. A positive Widal test result is not necessarily typhoid fever. Therefore, the results really need to be confirmed by other supporting examinations. IgM anti Salmonella IgG rapid test is one of the serological tests to support the diagnosis of typhoid fever which has better sensitivity and specificity to handle specific antibodies against Salmonella typhi in serum. This study aims to examine the results of the serological test of Immunoglobulin Miu (IgM) Anti Salmonella gamma immunoglobulin (IgG) on positive widal samples at Godean II Public Health Center and to see the lowest positive widal titers IgM antisalmonella in the sample. This research is a descriptive study with accidental sampling technique. The method of examination used a rapid test immunochromatography to examine IgM IgG anti Salmonella typhi on positive widal serum samples at Puskesmas Godean II, Sleman, DIY. The results showed that 21.7% of the samples were positive IgG negative IgM; 8.7% of IgM samples were positive IgG positive, and 69.6% IgM negative IgG negative. Anti Salmonella IgM in widal positive samples appeared at titer 320. Anti Salmonella typhi IgM and IgG were detected in positive widal samples at Godean II Public Health Center. Immunoglobulin Miu (IgM) appears at titer 320.